Construction of induced pluripotent stem cell line (ZZUi031-A) of a healthy young Chinese Han male - Shaohua Li (Elsevier, 2021)
We have successively constructed several induced pluripotent stem cell (iPSC) lines of middle-aged and elderly male, but cell samples from young donors are still scarce. In this project, we recruited a healthy 29-year-old Chinese Han male, obtained his skin fibroblasts and successfully established iPSC line using non-integrated reprogramming technology. The iPSC line showed normal karyotype, expressed pluripotency markers and differentiated into three germ layers in vivo. The cell line will serve as an available control in the research of pathological mechanisms of early-onset neurological diseases.